A comparative assessment of nursing students' cognitive knowledge of blood transfusion using lecture and simulation. Issue 1 (January 2016) - Flood, Lisa S.; Higbie, Julie
Abstract: Professional nurses must have the knowledge and skills to safely administer blood products and monitor for life-threatening complications. Nurse educators should ensure that student nurses also learn how to safely administer blood products; however students rarely have the opportunity to witness and manage adverse transfusion reactions. Despite the low incidence of rare adverse transfusion reactions, nursing students must be able to immediately recognize transfusion reactions, implement appropriate interventions, and communicate effectively with health care providers. To reinforce blood transfusion knowledge, practice technical skills, and promote management of adverse reactions, a human patient simulation experience was created for baccalaureate nursing students to provide application of related classroom content. Using a quasi-experimental design, students who received a related didactic lecture preceding the simulation were compared with students who did not receive the lecture. The lecture group's pre/posttest mean scores (n = 42) were significantly higher than the no lecture group's mean scores (n = 44). This simulation design included proper blood administration procedures, patient monitoring, management of transfusion reactions, and practice with interdisciplinary communication. Participation in a human patient simulation following a related didactic lecture may be useful to strengthen cognitive learning and help bridge the didactic-clinic gap. Highlights: Simulation provided students with standardized learning and the opportunity to witness rare blood transfusion reactions. Attending a related didactic lecture prior to the blood transfusion simulation seemed to improve students' knowledge. Human patient simulation after lecture may strengthen learning outcomes and help to bridge the didactic-clinic gap.